Dual-Path Implementation and Application of Parametric Design for Shield Tunnel Segments - Shi, Yifan (Scientific Journal of Technology, 2026)
To address the issues of low modeling efficiency and poor data-model associativity in shield tunnel engineering, this study explores two distinct BIM-based parametric modeling paths. The first path utilizes the Revit platform as a foundation, establishing a "data-program-component" collaborative drive mode through the Dynamo visual programming environment. This approach achieves the automated placement of segments under complex spatial poses by leveraging parametric adaptive families. The second path is based on the OpenRail platform, utilizing API-based custom development to encapsulate segment selection algorithms and detailed structural logic into integrated plugins. Comparative results demonstrate that the visual programming path offers high flexibility and logic transparency, making it highly suitable for customized projects with frequent design iterations. In contrast, the API-based plugin path excels in computational stability and standardization, catering to the requirements of large-scale production in mega-projects. The research findings provide a robust reference for achieving forward design and digital delivery in shield tunnel engineering.